Technology Introduction: Robots in Urosurgery - Hamal, Bhairab Kumar (Medical Journal of Shree Birendra Hospital, 2013)
Medical Journal of Shree Birendra Hospital; July-December 2012/vol.11/Issue2/2-3 DOI: http://dx.doi.org/10.3126/mjsbh.v11i2.7899